Given equations:
a) 3x-3=2x-2
b) -4x-1=3(-x)-2
c) -3x+6=2x+1
Let us solve them one by one.
a) 3x-3=2x-2
Adding 3 on both sides, we get
3x-3+3=2x-2+3
3x=2x
Subtracting 2x from both sides we get
3x-2x=2x-2x
x=0.
Therefore, only one solution 0.
b) -4x-1=3(-x)-2
Multiplying 3 and -x on right side, we get
-4x-1 =-3x -2.
Adding 1 on both sides, we get
-4x-1+1 =-3x -2+1
-4x =-3x-1
Adding 3x on both sides, we get
-4x+3x =-3x+3x-1
-x = -1.
Dividing both sides by -1.
-x/-1 = -1/-1
x=1.
Therefore, one solution 1.
c) -3x+6=2x+1
Subtracting 6 from both sides, we get
c) -3x+6-6=2x+1-6
-3x = 2x -5.
Subtracting 2x from both sides, we get
-3x-2x =2x-2x -5.
-5x =-5.
Dividing both sides by -5, we get
-5x/-5 = -5/-5
x=1.
Therefore, all equations has one solution.
Solution for first equation 0.
Solution for second equation 1.
Solution for third equation 1.